Preferential tax regimes with asymmetric countries - Sam Bucovetsky; Andreas Haufler (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
Current policy initiatives taken by the EU and the OECD aim at abolishing preferential corporate tax regimes. This note extends Keen's (2001) analysis of symmetric capital tax competition under preferential (or discriminatory) and non-discriminatory tax regimes to allow for countries of different size. Even though size asymmetries imply a redistribution of tax revenue from the larger to the smaller country, a non-discrimination policy is found to have similar effects as in the symmetric model: it lowers the average rate of capital taxation and thus makes tax competition more aggressive in both the large and the small country.
urn:nbn:de:bvb:19-epub-1209-1
Keywords: H73; H25; 330; corporate taxation; preferential tax regimes; Steuersystem; Unternehmensbesteuerung; Theorie; EU-Staaten; OECD-Staaten